The master plan: ISIS, al-Qaeda, and the Jihadi strategy for final victory - Fishman, Brian H. (Yale University Press, 2016)
"Drawing on troves of recently declassified documents captured from the Islamic State and its predecessors, counterterrorism expert Brian Fishman tells the story of this organization's complex and largely hidden past.- and what the master plan suggests about its future. Only by understanding the Islamic State's full history- and the strategy that drove it- can we understand the contradictions that may ultimately tear it apart" -- Dust jacket